2020
DOI: 10.1016/j.ijid.2020.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and validation of a risk score predicting risk of early-onset peritonitis among patients initializing peritoneal dialysis: A cohort study

Abstract: Early onset peritonitis (EOP) increases the risk of clinical complications in patients initializing peritoneal dialysis (PD). This study aimed to develop and validate a risk prediction model for EOP among patients initializing PD. Methods: 3772 patients registered with the Henan Peritoneal Dialysis Registry (HPDR) between 2007 and 2015 were included. The main outcome, EOP, was defined as incident peritonitis occurring within 6 months of the initialization of PD. Multivariable logistic regression modeling was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Few studies assessed the short-term effect of EOP [12,13,18,20,23], and one study found that the first episode of EOP had a higher cure rate, a lower rate of transfer to hemodialysis, and lower mortality than the first episode of LOP [15]. First, PD did not improve the last PDAP episode in the EOP group in our cohort, which may be due to underlying medical conditions and low residual renal function.…”
Section: Long-term Prognostic Outcomesmentioning
confidence: 79%
See 2 more Smart Citations
“…Few studies assessed the short-term effect of EOP [12,13,18,20,23], and one study found that the first episode of EOP had a higher cure rate, a lower rate of transfer to hemodialysis, and lower mortality than the first episode of LOP [15]. First, PD did not improve the last PDAP episode in the EOP group in our cohort, which may be due to underlying medical conditions and low residual renal function.…”
Section: Long-term Prognostic Outcomesmentioning
confidence: 79%
“…Older age was a risk factor for the first PDAP episode and a significant predictor of EOP in the final risk score. Although PD is suitable for elderly patients [5], EOP is an independent risk factor for mortality in this population [10,12,18]. Furthermore, EOP worsens the prognosis of PD [13,19,20], and age is positively correlated with poor physical health in elderly PD patients, potentially increasing the risk of peritonitis [21].…”
Section: Long-term Prognostic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation